Specialization within the ventral stream: the case for the visual word form area - Cohen, Laurent; Dehaene, Stanislas (NeuroImage (Orlando, Fla.), 2004)
Is there specialization for visual word recognition within the visual ventral stream of literate human adults? We review the evidence for a specialized “visual word form area” and critically examine some of the arguments recently placed against this hypothesis. Three distinct forms of specialization must be distinguished: functional specialization, reproducible localization, and regional selectivity. Examination of the literature with this theoretical division in mind indicates that reading activates a precise subpart of the left ventral occipitotemporal sulcus, and that patients with pure alexia consistently exhibit lesions of this region (reproducible localization). Second, this region implements processes adequate for reading in a specific script, such as invariance across upper- and lower-case letters, and its lesion results in the selective loss of reading-specific processes (functional specialization). Third, the issue of regional selectivity, namely, the existence of putative cortical patches dedicated to letter and word recognition, cannot be resolved by positron emission tomography or lesion data, but requires high-resolution neuroimaging techniques. The available evidence from single-subject fMRI and intracranial recordings suggests that some cortical sites respond preferentially to letter strings than to other categories of visual stimuli such as faces or objects, though the preference is often relative rather than absolute. We conclude that learning to read results in the progressive development of an inferotemporal region increasingly responsive to visual words, which is aptly named the visual word form area (VWFA).